2010
DOI: 10.1097/qai.0b013e3181ee3d82
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Safety and Virologic Efficacy of Maraviroc in Treatment-Experienced Patients With CCR5-Tropic HIV-1 Infection: 96-Week Combined Analysis of MOTIVATE 1 and 2

Abstract: Background Maraviroc, the first approved CCR5 antagonist, demonstrated 48-week safety and virologic efficacy in CCR5-tropic HIV-infected, treatment-experienced patients; however, critical longer-term safety and durability of responses are unknown. Methods Two-year follow-up of 2 prospective, randomized, blinded studies of maraviroc once daily or twice daily, or placebo in treatment-experienced patients with R5-tropic HIV-1 receiving an optimized background regimen. Unblinding occurred after the week-48 visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 17 publications
3
63
2
Order By: Relevance
“…[3][4][5] Consistent with data from other studies, 7,8,13,14 subgroup analysis demonstrated that virologic response rates increased with the number of active drugs in the ARV regimen. 4,6 Current guidelines recommend the use of at least two, and preferably three, fully active agents in a new regimen in patients with evidence of virologic resistance.…”
Section: -12supporting
confidence: 79%
See 1 more Smart Citation
“…[3][4][5] Consistent with data from other studies, 7,8,13,14 subgroup analysis demonstrated that virologic response rates increased with the number of active drugs in the ARV regimen. 4,6 Current guidelines recommend the use of at least two, and preferably three, fully active agents in a new regimen in patients with evidence of virologic resistance.…”
Section: -12supporting
confidence: 79%
“…The incidence of Category C AIDS-defining events and non-AIDSdefining malignancies was very low. This, together with data from the 96-week follow-up of the MOTIV-ATE studies 5 is reassuring in light of the lymphomas (and other cancers) reported in prior studies with another CCR5 antagonist. 17 Although individuals with the CCR5 delta 32 mutation are generally healthy, some immunological effects have been described, [18][19][20] raising concern at the time regarding the long-term safety of CCR5 antagonists.…”
Section: -12mentioning
confidence: 62%
“…At week 48, a similar proportion of patients with less than 50 copies HIV RNA/mL was achieved in the Maraviroc-treated group, as compare with that in the Efavirenz group (a reverse transcriptase inhibitor), but CD4 + cell count rebound was greater in patients received Maraviroc (Cooper et al, 2010). These observations were confirmed by week 96 analysis (Hardy et al, 2010;Sierra-Madero et al, 2010). The emergence of pre-existing CXCR4-tropic HIV-1 that failed to be detected in pre-treatment screening was related to virologic failure (Fatkenheuer et al, 2008;Cooper et al, 2010).…”
Section: Small Molecule Entry Inhibitorssupporting
confidence: 54%
“…In clinical trials, there was no statistically significant difference in these effects noted between placebo and maraviroc arms [113]. Increased aminotransferases were observed in maraviroc patients as compared with patients on non-maraviroc therapy, but no significant difference in the number of patients with large aminotransferase elevations.…”
Section: Maraviroc (Mvc)mentioning
confidence: 87%